16S rRNA Gene-Based Detection of Tetrachloroethene-Dechlorinating Desulfuromonas and Dehalococcoides Species - Löffler, Frank E. (American Society for Microbiology, 2000)
Members of the genera Desulfuromonas and Dehalococcoides reductively dechlorinate tetrachloroethene (PCE) and trichloroethene. Two primer pairs specific to hypervariable regions of the 16S rRNA genes of the Dehalococcoides group (comprising Dehalococcoides ethenogenes and Dehalococcoides sp. strain FL2) and the acetate-oxidizing, PCE-dechlorinating Desulfuromonas group (comprising Desulfuromonas sp. strain BB1 and Desulfuromonas chloroethenica) were designed. The detection threshold of a nested PCR approach using universal bacterial primers followed by a second PCR with the Desulfuromonas dechlorinator-targeted primer pair was 1 × 10(3) BB1 cells added per gram (wet weight) of sandy aquifer material. Total community DNA isolated from sediments of three Michigan rivers and six different chloroethene-contaminated aquifer samples was used as template in nested PCR. All river sediment samples yielded positive signals with the BB1- and the Dehalococcoides-targeted primers. One chloroethene-contaminated aquifer tested positive with the Dehalococcoides-targeted primers, and another contaminated aquifer tested positive with the Desulfuromonas dechlorinator-targeted primer pair. Restriction fragment analysis of the amplicons could discriminate strain BB1 from other known Desulfuromonas species. Microcosm studies confirmed the presence of PCE-dechlorinating, acetate-oxidizing Desulfuromonas and hydrogenotrophic Dehalococcoides species in samples yielding positive PCR signals with the specific primers.